Ненулевые периодические решения неавтономной системы дифференциальных уравнений второго порядка - Терехин, М.Т. (Український математичний журнал, 1994)
Доведено теореми, в яких основні умови існування ненульового пеіодичного розв'язку формулюються у термінах властивостей елементів матриці лінійного наближення системи. Theorems are proved, in which the main conditions for the existence of a nontrivial periodic solution are formulated in terms of the properties of the elements of a matrix of linear approximation to the system.